PROBLEMS OF VISUAL QUALITIES OF THE ARCHITECTURAL ENVIRONMENT IN GREEN STANDARDS - Holius, V. (Municipal economy of cities. Series: «Economy science», 2024)
The architectural community, which is closely involved in green standards, is already aware of the need to consider the aesthetic qualities of the architectural environment in rating systems of environmental certification. The study’s relevance is related to the need to find ways to factor the impact of the aesthetic component of architecture on human health in architectural projects. The purpose of the study is to justify the need to include the aesthetic properties of architectural objects under design in rating systems for environmental certification of architecture. Rating systems for environmental certification of buildings are not universal; each has its characteristics. Analysis of the most common systems shows that they do not take into account and do not regulate the appearance of buildings from the point of view of human visual perception. At the same time, the visual and aesthetic qualities of the architectural environment affect human health and well-being, which makes them components of ecology and a matter for consideration. The author’s research focuses on some of the most common and basic standards: LEED, BREEAM, and WELL. We determined that several green standards address the visual impact of architecture as a component of human health and ecology. We also found that during certification, according to the relevant standard, in most cases, the visual impact comes down to providing a view from the window, the level of lighting inside the room, and insolation, among others. At the same time, there is no regulation of the aesthetic impact of a building on a person; there is no methodology for its evaluation. There is an obvious need to consider the aesthetic qualities of architecture. Its quantification and scoring are possible within the framework of the corresponding credits of the environmental certification rating system. For this, we propose an appropriate technique, which consists of conducting a statistical survey of some categories of respondents who answer a series of questions about visual perception and give a generalised assessment of the architectural project. The study substantiates the expediency of introducing criteria for assessing the aesthetic properties of architectural structures into the system of green standards; it analyses the requirements of green standards regarding the aesthetic properties of the architectural environment. The article also develops the principles of forming criteria for assessing the aesthetic properties of architectural structures. It argues that the aesthetic visual qualities of architectural objects affect human health and that we should consider them in the environmental certification systems of architecture. Therefore, the study is forming a unified green standard template, one of the criteria of which will allow for the awarding of points for the visual environmental friendliness of a building undergoing green certification.